The Impact of El Nino on Rainfall Variability in Buleleng Regency (Case Study: Period 1995-2004) - Made Dwipayana; I Gede Putu Eka Suryana; I Gede Yudi Wisnawa (Tunas Geografi, 2023)
The climate in Indonesia usually runs yearly; there are times when a decrease in rainfall results in drought, and at other times, the rainfall increases resulting in flooding. One of the causes of changes in precipitation in Indonesia, including in most parts of the world, is ENSO (El Nino-Southern Oscillation), often called El Nino. This study aimed to determine the relationship between ENSO index data (SST Nino 3.4 anomaly) and monthly rainfall data in Buleleng Regency. This study uses secondary data, namely monthly rainfall data at 16 rain posts in Buleleng Regency and ENSO Index data from BMKG Region III Denpasar. Data were collected through observation, document recording and analyzed using statistical correlation methods.Â Furthermore, the results are processed spatially, namely by the Isohyet method. The research results show that the impact of El Nino on rainfall in Buleleng varies spatially and depends on the intensity of El Nino. In June-July-August (JJA/dry season) and September-October-November (SON/transition season), the impact of El Nino on rainfall variability in Buleleng Regency is more significant than other months, strong El Nino causes a decrease in rainfall in the majority of the Buleleng region with the characteristic of Below Normal rain (30% decrease in precipitation from the average), El Nino of weak - moderate intensity causes a reduction in rainfall in a small part of the Buleleng area with the dominant rain characteristic of Below Normal.Keywords: El Nino, Precipitation Variability, and Correlation Index.